Great flicks scientific studies of cinematic creativity and aesthetics - Simonton, Dean Keith (New York ; Oxford : Oxford University Press, 2011)
This text explores movie awards, including the Oscars and Golden Globes, and how those awards relate to critical acclaim. It also studies more closely how these awards cluster together and which of these clusters best predict cinematic success.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Motion pictures; Motion pictures -- Aesthetics; Creation (Literary, artistic, etc.)